A review of dolomite catalyst for biomass gasification tar removal. (1st May 2020) - Islam, Md Waliul
Abstract: Biomass gasification derived syngas could be used for different important industrial applications such as running internal combustion engine, generating electricity, and producing liquid hydrocarbon by Fisher-Tropsch method. The major drawback of syngas production through biomass gasification is the presence of contaminants such as hydrogen sulfide, hydrogen chloride, particulate matter, tar, and other undesired compounds in syngas. Tar is the most difficult to remove from syngas among all of the contaminants and causes severe problems in the downstream syngas applications. Researchers have been investigating different catalysts for removing tars for the last several decades. Dolomite is one of the widely studied catalysts for removing tar from syngas. Numerous research works have been conducted on the effectiveness of dolomite, calcined dolomite and combination of dolomite with other catalysts for removing tar from syngas. In this review, a detailed study on the dolomite catalyst has been conducted. Different aspects of dolomite catalyst such as calcination, mechanism of catalysis, in-situ vs ex-situ use, major problems (attrition, elutriation and coke formation), comparative strength, and the effectiveness of dolomite when used in combination with other catalysts have been studied and presented.